Analisis Analisis Perlindungan Hukum Bagi Pelaku Usaha Rental Mobil Terhadap Resiko Penipuan Oleh Penyewa Di Kota Kupang - Adoe, Geraldy Hendriko Gracio; Manafe, Deddy; sonbait, sigit (Artemis Law Journal, 2025)
This study analyzes the legal protection available to car rental business actors in Kupang City against the risk of fraud by tenants. As demand for car rentals rises, business owners face growing challenges, including tenants failing to return vehicles, using fake identities, or returning cars late. Using empirical legal methods, the study identifies common fraudulent practices and highlights the increased vulnerability of business actors when rental agreements are made without formal contracts. The absence of clear legal documentation complicates efforts to seek compensation in cases of agreement violations. Several real-life cases show that fraud, such as theft or false damage claims, has caused significant financial losses. The study also explores legal remedies and preventive strategies, including using detailed rental contracts, verifying tenant identities, requiring advance payments, and installing GPS tracking systems in vehicles. Although current legal protections are generally sufficient, enforcement remains a key challenge. The study concludes that effective legal safeguards are crucial for the sustainability of car rental businesses. It recommends that business actors always use formal contracts and promote legal awareness among tenants. By doing so, they can better manage fraud risks and reduce potential losses. This research aims to contribute to both legal scholarship and practical improvements in the car rental industry, offering guidance to business actors in addressing the legal and operational risks associated with fraudulent rental practices.